(untitled) (The International Journal of Educational Sciences and Arts, 2023)
The scientific change that the current era is witnessing in the field of informatics and informational development and the implications of that progress in all branches of knowledge imposed new variables that affected all aspects of life, and changed many of its patterns and methods to which society must respond. The future requires people with multiple abilities and skills to be able to communicate with others and interact with the changes of the times through advanced modern technical means until it reaches e-learning, which has become an urgent necessity through which the future is predicted. E-learning aims to provide multiple and disparate sources of information that provide opportunities for comparison, discussion, analysis, and evaluation using electronic media in linking and interacting with the educational system while providing the opportunity for learners to interact instantly electronically with each other on one hand, and between them and the teacher on the other hand through modern technological resources/media. The problem with the research is that the institutions that produce the electronic stories for the kindergarten stage do not adhere to the standards necessary to produce these stories for the kindergarten stage. Therefore, the importance of the research stands out in developing a proposed model for the design and production standards of the electronic story for the kindergarten stage.